رأي الطلبة املاليزيني يف اسرتاتيجيات تدريس اللغة العربية باستخدام تدريبات الرتمجة داخل الفصل: دراسة حتليلية = Students’ response to the strategy of employing translation in teaching second language in the classroom: an analysis = Maklum balas pelajar kepada strategi penggunaan terjemahan dalam pengajaran bahasa kedua dalam bilik darjah: satu analisa - Abd. Rahman, Akmal Khuzairy; Abbas, Asiah (IIUM Press, International Islamic University Malaysia, 2016)
The study analyses feedbacks from questionnaires from a group Malaysian Arabic learners after engaging them with Arabic teaching strategies that made use of translation exercises in order to know their views on the use of the strategies and the advantages they gained in improving their class room learning environment of Arabic. The teaching strategies include the following steps: preparing the translation exercises to know their answers and analysing the errors on the word, phrase and sentence level; the errors were presented and discussed in the classroom; the errors were explained to make them aware of the means to avoid them. This was done by explaining the linguistic differences between Malay and Arabic that were attributable to those mistakes that were resulted from direct or literal translation or lack of knowledge in connotations of words, meanings and contexts. Afterwards, questionnaires were distributed to know their view on the teaching strategies used in improving their classroom Arabic teaching environment. The answers from the questionnaires revealed the following: distributing the exercises, collecting them and analysing the answers. Students were engaged in discussion and the errors committed were explained and corrected. Questionnaire to know their perception on the effectiveness of the strategy was distributed and analysed. The study concluded, among others: that there are positive aspects of the teaching strategies using translation exercises in teaching Arabic as second language as they help the students to become more aware of the pitfalls of direct translation and their lack of knowledge in the linguistic differences in the connotations, meanings and contexts of words, phrase and sentences. The strategies also managed to encourage them to self study, an experience that helps them to enrich knowledge in Arabic vocabularies, grammar and morphology and sentence styles. *********************************************************** Kajian ini bertujuan untuk meninjau maklum balas pelajar kepada keberkesanan penggunaan terjemahan seabgai satu cara untuk menguasai kemahiran bahasa Arab sebagai bahasa kedua dalam suasana pembelajaran dalam darjah. Perancangan strategi pengajaran merangkumi: penyediaan latihan-latihan yang memfokuskan kepada perkataan, frasa dan ayat; mengagihkan latihan, pungutan kembali latihan dan analisa jawapan serta rumusan. Para pelajar dilibatkan dalam perbincangan kesalahan dan sebab-sebabnya didedahkan. Pada peringkat akhirnya, soal-selidik diberikan kepada mereka untuk mengetahui persepsi mereka tentang keberkesanan strategi tersebut. Analisa jawapan soal selidik tersebut merumuskan: Terdapat aspek yang menggalakkan dalam penggunaan terjemahan sebagai strategi pengajaran bahasa kerana ia menolong meningkatkan kemahiran dan kesedaran pelajar untuk mengelak melakukan kesalahan; keberkesanan terjemahan sebagai strategi pengajaran tidak hanya tehad kepada empat kemahiran utama bahasa (mendengar, menulis, bertutur, membaca) tetapi turut memberi kesan terhadap aspek-aspek lain bahasa seperti penambahan kosa kata, penambahbaikan aspek tatabahasa, saraf dan stail penulisan.